2017
DOI: 10.1002/ijgo.12380
|View full text |Cite
|
Sign up to set email alerts
|

The communication and emotional support needs to improve women's experience of childbirth care in health facilities in Southwest Nigeria: A qualitative study

Abstract: Conclusion:To increase, improve, and sustain facility-based childbirth in Nigeria, health systems should appreciate the uniqueness and importance of each woman's needs during childbirth. Practical and sustainable actions should be taken to meet these needs, within the confines of the acceptable sociocultural norms. K E Y W O R D S

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 37 publications
1
66
0
1
Order By: Relevance
“…The protocol for the study was agreed before data collection began and country‐specific analyses explain the site‐specific study methodology, strengths, and limitations in more detail.…”
Section: Methodsmentioning
confidence: 99%
“…The protocol for the study was agreed before data collection began and country‐specific analyses explain the site‐specific study methodology, strengths, and limitations in more detail.…”
Section: Methodsmentioning
confidence: 99%
“…A primary qualitative study was conducted in eight study facilities and facility catchment areas in Nigeria and Uganda. Detailed accounts of the study methods, procedures and results have been published separately . Briefly, in‐depth interviews (IDIs) and focus group discussions (FGDs) were conducted with women of reproductive age who had given birth in a health facility in the previous 12 months, as well as doctors, nurses/midwives, and healthcare administrators working in the study facilities.…”
Section: Methodsmentioning
confidence: 99%
“…While the data are situated in the local health systems, the contextual enablers and barriers are common to many low‐resource maternity care facilities. The richness of data from multiple perspectives provided a comprehensive view on labor monitoring from the key stakeholders, and supplements the findings from other papers in this Supplement . This study may have been limited by the self‐reported practices from the health professionals, which can lead to social desirability bias, resulting in a narrative of “ideal situation” rather than the “actual situation” of labor monitoring.…”
Section: Discussionmentioning
confidence: 81%
“…Only Health Center III and above levels have the capacity to provide maternity services. More details of the study settings can be found in the study protocol and country‐specific analyses in this Supplement . Facilities were chosen based on the following criteria: (1) having at least 1000 births per year; (2) being a major healthcare facility in the region; (3) not being a primary health unit; (4) having relatively stable access to skilled birth attendants, and to the provision of cesarean delivery, augmentation of labor, assisted vaginal birth, and good intrapartum care practices …”
Section: Methodsmentioning
confidence: 99%